Violence witnessing, perpetrating and victimization in medellin, Colombia: a random population survey - Restrepo Alexandra; Montoya Nilton E; Duque Luis F (BMC, 2011)
Abstract Background The burden of injury from violence and the costs attributable to violence are extremely high in Colombia. Despite a dramatic decline in homicides over the last ten years, homicide rate in Medellin, Colombia second largest city continues to rank among the highest of cities in Latin America. This study aims to estimate the prevalence and distribution of witnesses, victims and perpetrators of different forms of interpersonal violence in a representative sample of the general population in Medellin in 2007. Methods A face-to-face survey was carried out on a random selected, non-institutionalized population aged 12 to 60 years, with a response rate of 91% yielding 2,095 interview responses. Results We present the rates of prevalence for having been a witness, victim, or perpetrator for different forms of violence standardized using the WHO truncated population pyramid to allow for cross-national comparison. We also present data on verbal aggression, fraud and deception, yelling and heavy pranks, unarmed aggression during last year, and armed threat, other severe threats, robbery, armed physical aggression, and sexual aggression during the lifetime, by age, sex, marital and socioeconomic status, and education. Men reported the highest prevalence of being victims, perpetrators and witnesses in all forms of violence, except for robbery and sexual violence. The number of victims per perpetrator was positively correlated with the severity of the type of violence. The highest victimization proportions over the previous twelve months occurred among minors. Perpetrators are typically young unmarried males from lower socio-economic strata. Conclusions Due to very low proportion of victimization report to authorities, periodic surveys should be included in systems for epidemiological monitoring of violence, not only of victimization but also for perpetrators. Victimization information allows quantifying the magnitude of different forms of violence, while data on factors associated with aggression and perpetrators are necessary to estimate risk and protective factors that are essential to sound policies for violence prevention formulation.